Discovering objects and services in context-aware IoT environments. (30th May 2019) - Wang, Wei; Lee, Kevin; Murray, David; Guo, Jian
The future IoT is expected to connect trillions of objects across infrastructures and domains worldwide. Compared to traditional web applications, the context of objects, such as dynamic object property values, may rapidly change. Browsing web pages with hyperlinks is unsuitable for representing and discovering the dynamic state of objects and services in the IoT, as the dynamic context is less keyword-rich than the relatively static contents on traditional web pages. This paper reviews state-of-the-art in discovering objects and services in the current IoT, and analyses the constraints. This paper also proposes a discovery mechanism, which is extended from previous work GGIoT. The proposed discovery mechanism is aware of dynamic context change in the IoT, and can improve the discovery process using automation.